Management of Pregnant Women with Atrial Septal Defect and Pulmonary Hypertension: A Case Report - Wicaksono, Arif; Martini, Heny; Rizal, Ardian; Rahimah, Anna Fuji (Heart Science Journal, 2024)
Backgrounds:Pulmonary Hypertension (PH) is a condition where there is an increase in Pulmonary Vascular Resistance (PVR) and an increase in the mean Pulmonary Arterial Pressure (mPAP) to more than 20 mmHg. PH can occur in someone with Congenital Heart Disease (CHD). PH conditions can aggravate pregnancy in women with CHD. So that women with PH are recommended not to undergo pregnancy. However, it is possible for women with CHD with PH conditions to undergo pregnancy. In these conditions, optimizing PH therapy is important so that pregnant women with PH do not experience a worsening of the condition and can carry out their pregnancy well until delivery.Â Case Presentations:A 38-year-old female patient with a history of Atrial Septal Defect-Pulmonary Hypertension came for routine control to the cardiac clinic with the condition of pregnancy of her 4th child who was just discovered when she was 6 months pregnant. Since giving birth to her third child, the patient began to complain of being easily tired when doing activities accompanied by swollen legs that disappeared with rest. At that time, the patient went to a cardiologist for an echocardiography examination and was diagnosed as Atrial Septal Defect (ASD)-Pulmonary Hypertension (PH). Since then, the patient has been routinely treated at a cardiologist with Pulmonary Hypertension drugs, including Phospodiesterase5 (PDE5) inhibitors (Sildenafil) and Prostacyclin Analogue (Dorner). The patient had done Transesophageal Echocardiography (TEE) with the results of ASD secundum suitable for closure by device. Patients with Right Heart Catheterization (RHC) results, ASD secundum with PH High Flow High Resistance reactive to Vasoreactivity Test. Since the patient was found to be pregnant, the patient continued to use Sildenafil and discontinued the use of Dorner. The patient then continued treatment in a multidisciplinary team.Â Conclusion :Management of pregnant women with CHD and PH is important because the condition of PH itself further aggravates the condition of pregnancy. Medical management for PH in pregnant women follows the guidelines for the safety of drugs in pregnancy. So that the choice of therapy is crucial related to the goal of treatment to control the PH condition in the patient but still pay attention to safety in pregnancy conditions.